2018
DOI: 10.1002/elps.201800122
|View full text |Cite
|
Sign up to set email alerts
|

Development of green extraction processes for Nannochloropsis gaditana biomass valorization

Abstract: In the present work, the valorization of Nannochloropsis gaditana biomass is proposed within the concept of biorefinery. To this aim, high-pressure homogenization (HPH) was used to break down the strong cell wall and supercritical fluid extraction (SFE) with pure CO was applied as a first step to extract valuable compounds (such as non-polar lipids and pigments). Extraction of the remaining residue for the recovery of bioactive compounds was studied by means of an experimental design based on response surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…Similarly, da Costa Rodriguez research group studied the effect of solvent composition of rice bran oil extracted with ethanol containing different water contents at 60–90 °C and concluded that there were no major differences in the lipid composition present in the extracts [ 42 ]. The use of PLE with green solvents (water and ethanol) for the extraction of bioactives from the microalgae Nannochloropsis gaditana and Phaeodactylum tricornutum was recently investigated [ 43 , 44 ]. Despite the optimum extraction conditions was achieved with pure ethanol, FAs such as palmitoleic, palmitic, myristic acids and EPA were predominant in all PLE extracts from Nannochloropsis gaditana [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, da Costa Rodriguez research group studied the effect of solvent composition of rice bran oil extracted with ethanol containing different water contents at 60–90 °C and concluded that there were no major differences in the lipid composition present in the extracts [ 42 ]. The use of PLE with green solvents (water and ethanol) for the extraction of bioactives from the microalgae Nannochloropsis gaditana and Phaeodactylum tricornutum was recently investigated [ 43 , 44 ]. Despite the optimum extraction conditions was achieved with pure ethanol, FAs such as palmitoleic, palmitic, myristic acids and EPA were predominant in all PLE extracts from Nannochloropsis gaditana [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…The use of PLE with green solvents (water and ethanol) for the extraction of bioactives from the microalgae Nannochloropsis gaditana and Phaeodactylum tricornutum was recently investigated [ 43 , 44 ]. Despite the optimum extraction conditions was achieved with pure ethanol, FAs such as palmitoleic, palmitic, myristic acids and EPA were predominant in all PLE extracts from Nannochloropsis gaditana [ 43 ]. The PLE of F. vesiculosus algae carried out in this work showed that different solvents produced extracts with different FAs content and therefore, the possibility of using PLE as a selective technique for the extraction of specific carbon number fatty acids.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, non-polar compounds (such as TG) were extracted in the first step whereas mid-polar compounds and polar compounds (almost pigments) were extracted in the following steps. A similar approach was carried out by Sánchez-Camargo et al [132]. In this study, previous high-pressure homogenization (HPH) prior extraction was performed to Nannochloropsis gaditana biomass in order to break or weaken the cell wall and to foster a better extraction of its components.…”
Section: Extraction Of Bioactive Compounds From Seaweeds and Microalgaementioning
confidence: 99%
“…Greater antioxidant capacities than the ones estimated in this work have been described for extracts rich in bioactive components. For instance, antioxidant activities of 100-600 µmol TE/g sample have been described for Scenedesmus obliquus extracts rich in carotenoids [49] and Nannochloropsis gaditana extracts rich in carotenoids, chlorophylls and polar lipids have been reported to possess antioxidant capacities of 300-800 µmol TE/g sample [50]. This indicates that most of the compounds responsible for the high antioxidant potential of microalgae are intracellular components.…”
Section: Chemical Composition Of Microalgae Before and After Ultrasound Treatmentmentioning
confidence: 99%